2004
DOI: 10.1023/b:orig.0000029883.18365.af
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Carbon Dioxide on Pyrite as a Pathway for Abiogenic Formation of Organic Molecules

Abstract: A wide spectrum of electrode potentials of minerals that compose sulfide ores enables the latter, when in contact with hydrothermal solutions, to form galvanic pairs with cathode potentials sufficient for electrochemical reduction of CO2. The experiments performed demonstrated the increase of cathode current on the rotating pyrite disc electrode in a range of potentials more negative than -800 mV in presence of CO2. In high-pressure experiments performed in a specially designed electrochemical cell equipped wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 2 publications
5
30
0
Order By: Relevance
“…11 A recent study has highlighted the catalytic nature of greigite, showing that CO 2 could be converted to CH 4 and CO, but no solution-based products were detected in that study -an essential requirement for prebiotic chemistry. 12 In addition, FeS has been shown to catalyze CO 2 reduction 13 and into a range of thiols in the presence of H 2 S. 14 In this study, we show that CO 2 can be reduced to a range of small organic solution-based molecules that are required for the commencement of pre-biotic chemistry. The use of a greigite surface allows such transformations at a low overpotential, atmospheric pressure and room temperature.…”
mentioning
confidence: 63%
“…11 A recent study has highlighted the catalytic nature of greigite, showing that CO 2 could be converted to CH 4 and CO, but no solution-based products were detected in that study -an essential requirement for prebiotic chemistry. 12 In addition, FeS has been shown to catalyze CO 2 reduction 13 and into a range of thiols in the presence of H 2 S. 14 In this study, we show that CO 2 can be reduced to a range of small organic solution-based molecules that are required for the commencement of pre-biotic chemistry. The use of a greigite surface allows such transformations at a low overpotential, atmospheric pressure and room temperature.…”
mentioning
confidence: 63%
“…Abiotic formation and accumulation of organic matter on Earth might occur in hydrothermal systems (Corliss et al, 1981;Holm, 1992a;Shock, 1993;Yanagawa, 1980;Vladimirov et al, 2004). Thus, hydrothermal settings may provide organic compound precursors for the evolution of life on Earth (Amend and Shock, 1998;Baross and Hoffman, 1985;Ferris, 1992;Hennet et al, 1992;Holm, 1992b;Marshall, 1994;Ozawa et al, 2004;Shock, 1990;Simoneit, 1992Simoneit, , 1995.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by the finding that iron and copper sulphide minerals (pyrrhotite, pyrite, covellite, bornite, chalcopyrite, tetrahedrite) proved to be efficient catalysts in converting formamide (H 2 NCHO) into purine, adenine, and other heterocyclic bases under simulated prebiotic conditions. 146 It was also shown that pyrite and greigite (Fe 3 S 4 ) catalyse CO 2 reduction, converting it respectively into formate 147 and methanol, formic, acetic and pyruvic acid.…”
Section: Reactions On Sulphide Surfacesmentioning
confidence: 99%